2021
DOI: 10.1002/ar.24827
|View full text |Cite
|
Sign up to set email alerts
|

Cranial functional morphology of the pseudosuchian Effigia and implications for its ecological role in the Triassic

Abstract: Pseudosuchians, archosaurian reptiles more closely related to crocodylians than to birds, exhibited high morphological diversity during the Triassic with numerous examples of morphological convergence described between Triassic pseudosuchians and post‐Triassic dinosaurs. One example is the shuvosaurid Effigia okeeffeae which exhibits an “ostrich‐like” bauplan comprising a gracile skeleton with edentulous jaws and large orbits, similar to ornithomimid dinosaurs and extant palaeognaths. This bauplan is regarded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 110 publications
2
13
0
Order By: Relevance
“…Furthermore, the Saurosuchus vomers are much thinner than in Allosaurus , which is the likely cause of the higher observed stresses from the palate of the pseudosuchian during both biting simulations. These results provide another example where similar form between distantly related extinct taxa does not equate to the same functional morphologies (Bestwick et al, 2022; Ferry‐Graham et al, 2002; Fisher, 1985; Lautenschlager et al, 2016; Thomason, 1995).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Furthermore, the Saurosuchus vomers are much thinner than in Allosaurus , which is the likely cause of the higher observed stresses from the palate of the pseudosuchian during both biting simulations. These results provide another example where similar form between distantly related extinct taxa does not equate to the same functional morphologies (Bestwick et al, 2022; Ferry‐Graham et al, 2002; Fisher, 1985; Lautenschlager et al, 2016; Thomason, 1995).…”
Section: Discussionmentioning
confidence: 86%
“…Muscle origination sites on the Saurosuchus cranium (Figure 2) were identified for each jaw adductor muscle independently based on osteological correlates such as muscle scars, ridges and depressions. Muscle insertion sites on the adjusted mandible (Figure 2) were based on the same criteria, assuming a largely similar jaw adductor arrangement across archosaurs following von Baczko (2018), Bestwick et al (2022), and Holliday (2009). As a first step, the origin and insertion sites of each muscle were connected by individual point‐to‐point connections.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sharing the Triassic ecosystems with Aetosaurs and other crocodylomorphs were the beaked, edentulous shuvosaurs like Effigia okeeffeae (Nesbitt, 2007). Here, Bestwick et al (2022) use 3D modeling and engineering approaches to test hypotheses of feeding function in these enigmatic animals. The authors found that Effigia had a rather weakly built skull and was likely a specialist that fed on soft plant material, making it among the most divergently‐adapted species of crocodylomorphs.…”
Section: Figurementioning
confidence: 99%